重型再生障碍性贫血行异基因造血干细胞移植后植入功能不良的危险因素分析 - Mamal, A (Zhonghua Xue Ye Xue Za Zhi, 2017)
OBJECTIVE: To investigate the risk factors of poor graft function (PGF) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) for severe aplastic anemia (SAA). METHODS: Clinical data from 111 SAA patients who received allo-HSCT were analyzed retrospectively. Factors including age, gender, interval to transplantation, the level of serum ferritin before transplantation were analyzed by Cox multivariate regression analysis. RESULTS: Among the 111 patients who underwent allo-HSCT, 16 developed PGF (14.4%). Multivariate analysis showed donor type (HR=2.656, 95%CI 1.204–5.858, P= 0.016) and the level of serum ferritin before tansplantation (HR=3.170, 95%CI 1.400–7.180, P=0.006) were significant risk factors for PGF. CONCLUSION: Unrelated donor transplantation and the high level of serum ferritin before transplantation are risk factors for PGF.